Cardiac Tissue Chips (CTCs) for Modeling Cardiovascular Disease - Rogers, Aaron J.; Miller, Jessica M.; Kannappan, Ramaswamy; Sethu, Palaniappan (IEEE transactions on biomedical engineering, 2019)
Objective: Cardiovascular research and regenerative strategies have been significantly limited by the lack of relevant cell culture models that can recreate complex hemodynamic stresses associated with pressure-volume changes in the heart. Methods: To address this issue, we designed a biomimetic cardiac tissue chip (CTC) model where encapsulated cardiac cells can be cultured in three-dimensional (3-D) fibres and subjected to hemodynamic loading to mimic pressure-volume changes seen in the left ventricle. These 3-D fibres are suspended within a microfluidic chamber between two posts and integrated within a flow loop. Various parameters associated with heart function, like heart rate, peak-systolic pressure, end-diastolic pressure and volume, end-systolic pressure and volume, and duration ratio between systolic and diastolic, can all be precisely manipulated, allowing culture of cardiac cells under developmental, normal, and disease states. Results: We describe two examples of how the CTC can significantly impact cardiovascular research by reproducing the pathophysiological mechanical stresses associated with pressure overload and volume overload. Our results using H9c2 cells, a cardiomyogenic cell line, clearly show that culture within the CTC under pathological hemodynamic loads accurately induces morphological and gene expression changes, similar to those seen in both hypertrophic and dilated cardiomyopathy. Under pressure overload, the cells within the CTC see increased hypertrophic remodeling and fibrosis, whereas cells subject to prolonged volume overload experience significant changes to cellular aspect ratio through thinning and elongation of the engineered tissue. Conclusions: These results demonstrate that the CTC can be used to create highly relevant models where hemodynamic loading and unloading are accurately reproduced for cardiovascular disease modeling.